2012
DOI: 10.1007/s10658-012-0113-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of pre-harvest brown rot epidemics within individual peach tree canopies

Abstract: Tree canopies are architecturally complex and pose several challenges for measuring and characterizing spatial patterns of disease. Recently developed methods for fine-scale canopy mapping and three-dimensional spatial pattern analysis were applied in a 3-year study to characterize spatio-temporal development of pre-harvest brown rot of peach, caused by Monilinia fructicola, in 13 trees of different maturity classes. We observed a negative correlation between an index of disease aggregation and disease inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…It is well established that brown rot incidence on blighted blossoms is directly correlated with the subsequent disease stages leading to twig or fruit blight and to fruit rots (Stensvand et al ., ; Everhart et al ., ; Holb et al ., ). Therefore, the observed predominance of M. laxa on blighted blossoms of all four hosts in the current study suggested that it would be the predominant species on the decayed fruit.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that brown rot incidence on blighted blossoms is directly correlated with the subsequent disease stages leading to twig or fruit blight and to fruit rots (Stensvand et al ., ; Everhart et al ., ; Holb et al ., ). Therefore, the observed predominance of M. laxa on blighted blossoms of all four hosts in the current study suggested that it would be the predominant species on the decayed fruit.…”
Section: Discussionmentioning
confidence: 99%
“…They have proven effective in securing that fruit reach storage and distribution in the cleanest possible conditions. Similarly, disease monitoring pre-harvest represents another strategy that provides guidance for specific treatments later on during post-harvest [41]. In addition, the use of biocontrol is a robust and effective method that serves to protect both the plant during growth and the fruit post-harvest [42].…”
Section: Current Knowledge Of Disease Protectionmentioning
confidence: 99%
“…In plant pathology K-S test have been utilized by Lescure et al, (1992), Lin et al, (2004), Camarero et al, (2005) Freita-Nunes and Rocha (2007), Carneiro (2009) and Everhart et al, (2011). Everhart et al, (2012) used this for spatio-temporal patterns of pre-harvest brown rot epidemics within individual peach tree canopies. This approach also used for host-pathogen like Prunus persica-Monilinia fructicola, Prunus cerasus-Monilinia laxa and Triticum aestivum "WPB926-Rhizoctonia oryzae.…”
Section: Thementioning
confidence: 99%
“…Kelly and Meentemeyer (2002) used this as a supportive tool for study the landscape dynamics of the spread of sudden oak death (Lithocarpus densiflorus-Phytophthora ramorum) in California. For Citrus black spot-Guignardia citricarpa and Prunus persica-Monilinia fructicola this procedure was utilized by Sposito et al, (2008) and Everhart et al, (2012), respectively. Gent et al, (2007) used this technique to determine the probability of classifying mean disease incidence for Humulus lupulus-Podosphaera macularis.…”
Section: Thementioning
confidence: 99%